Detecting Ponzi finance: An evolutionary approach to the measure of financial fragility - Éric Tymoigne (Levy Economics Institute of Bard College, 2010)
Different frameworks of analysis lead to different conceptions of financial instability and financial fragility. On one side, the static approach conceptualizes financial instability as an unfortunate byproduct of capitalism that results from unpredictable random forces that no one can do anything about except prepare for through adequate loss reserves, capital, and liquidation buffers. On the other side, the evolutionary approach conceptualizes financial instability as something that the current economic system invariably brings upon itself through internal market and nonmarket forces, and that requires change in financial practices rather than merely good financial buffers. This paper compares the two approaches in order to lay the foundation for the empirical analysis developed within the evolutionary approach. The paper shows that, with the use of macroeconomic data, it is possible to detect financial fragility, especially Ponzi finance. The methodology is applied to residential housing in the U.S. household sector and is able to capture some of the trends that are known to be sources of economic difficulties. Notably, the paper finds that Ponzi finance was going on in the housing sector from at least 2004 to 2007, which concurs with other works based on more detailed data.
Keywords: E12; E32; G01; 330; financial fragility; financial crisis; financial policy; Minsky